PERFORMANCE ANALYSIS OF EMPLOYEES AT SHOP AISYAH MART GORONTALO CITY - Agus Didan Purwanto (Journal of Economic, Business, and Administration (JEBA), 2023)
The research objectives include to find out and analyze the performance of employees at the Aisyah Mart Store, Gorontalo City. To find out the factors that determine employee performance at the Aisyah Mart Store, Gorontalo City. While the research approach is the method used by researchers to master and develop science with the highest validity and accuracy as a reference in research. The purpose of this research approach is to obtain in-depth data, a data that contains meaning. The results of the study conclude the analysis of employee analysis at the Aisyah mart store, Gorontalo city, namely 1. Based on the results of the research and interviews conducted, the researchers concluded that the performance of employees at the Aisyah mart store in Gorontalo City was maximized. However, there is still a lack of direction from managers on policies or procedures so that it has an impact on elements of work culture, and they seem to be negligent of their responsibilities. 2. The determining factors that need to be done to improve employee performance at the Aisyah mart Store Gorontalo City are: Rewards, Motivation, Work Environment, Leadership. 3. What is still lacking and needs attention is the provision of rewards and punishments to employees who are able to achieve certain targets. so that it can then be a source of motivation for employees to be able to work optimally.